Exlibris Dr Enrique Sáez Fernández-Cesariego / Roland Roveda. - Roveda, Roland (1912-1996) ([wydawca nieznany], 1961)
W obramowaniu inicjały E. S. F. C. niżej napis: Exlibris Dr Enrique Sáez Fernández-Cesariego.